2015
DOI: 10.13080/z-a.2015.102.037
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active phenolic compounds in buckwheat, oats and winter spelt wheat

Abstract: The current study was aimed to determine the total phenolic content and antioxidant activity, rutin, quercetin and phenolic acids content in buckwheat, husked and common oats, winter spelt, winter and spring wheat grain with and without husks or glume, only husks or glume as well as to estimate phenolic compounds ratio and to compare their distribution between cereal grain and husks or glume. In this way to ascertain the losses of phenolic compounds in grain which will be used for food production. Total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
3
17
0
1
Order By: Relevance
“…Literature reports that antioxidant activity correlates significantly with the total phenolic concentration (Kerienë et al, 2015). Similar tendencies were observed in this study, where Raw-BF had the highest total phenolic concentration and the highest DPPHÿ radical scavenging activity (27.17 mM TE·100 g -1 DM) among the flour samples.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Literature reports that antioxidant activity correlates significantly with the total phenolic concentration (Kerienë et al, 2015). Similar tendencies were observed in this study, where Raw-BF had the highest total phenolic concentration and the highest DPPHÿ radical scavenging activity (27.17 mM TE·100 g -1 DM) among the flour samples.…”
Section: Resultssupporting
confidence: 90%
“…This confirms the results of Li et al (2013). Literature indicates that there is a positive correlation between the rutin and total phenolic concentration of buckwheat grain with husks (Kerienë et al, 2015). The current study did not confirm this, as Dark-BF had the highest rutin concentration, whereas Raw-BF had the highest total phenolic concentration among the buckwheat flour samples.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, the content of major phenolic acids was higher in covered genotypes. Our results partially agreed with a finding that cereal hulls contain significantly higher total polyphenol and most phenolic acid content if compared to cereal grain (Kerienė et al, 2015). Gamel and Abdel-Aal (2012) show the highest concentration of phenolic acids (especially ferulic, p-coumaric and syringic acids) in covered barley hulls followed by outer layers of grain (pericarp and testa) and decreasing towards endosperm.…”
Section: Discussionsupporting
confidence: 92%
“…Different solvents used for the Total phenolic content in antifungal extracts preparation of bee product extracts did not have significant effect, therefore, inTable 1we presented average TPCs determined in ethanol and DMSO solvents.Our results agree with those ofSpulber, Colța, et al (2017);Spulber, Doğaroğlu, et al (2017), who suggest that propolis and bee pollen are considered the main bee products with the highest amounts of phenolic compounds and different solvent applied for bioactive substances extraction from bee products do not present significant differences. Our previous studies have shown that buckwheat grain and hulls have the highest amount of total phenolic compounds with the highest antioxidant activity, compared with other cereal grain (Kerienė et al, 2015). The content of individual phenolic compounds in the total phenolics in buckwheat grain and other parts of grain and plant depends on the soil type, cultivation region, and…”
mentioning
confidence: 99%